Effects of Crosslinker and Silicon to Enhance Taber Abrasion and Physical Properties of Finished Leather for Upholstery Furniture - Atiqa Rahmawati; Elis Nurbalia; Rini Tiyastuti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Finishing is one of the stages in leather processing. The addition of silicone and crosslinker in the top coat of the finishing stage of leather upholstery furniture is used to increase abrasion resistance, which is a critical factor in determining the life and quality of leather furniture. The aim of this study was to determine the influence of silicone and crosslinker additions on the abrasion resistance and physical properties of leather upholstery furniture. The leather material used is dyed crust leather with a thickness of 1.2-1.4 mm with an area of 1.5 sqft. The addition of crosslinker and silicone is applied only to the top coat. The analyses performed include physical skin analysis (adhesion test, rubbing fastness, glossy test, and flexing) and organoleptic tests (abrasion and smoothness tests). The addition of crosslinker and silicone can affect the physical and organoleptic quality of leather. The addition of crosslinker and silicone to the top coat showed the best results on upholstery leather sample D (3% crosslinker and 4% silicone).The results of statistical tests using the multinomial logistic regression method in organoleptic testing and ANOVA in physical testing showed that only crosslinker had a significant effect on the response.Â